PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK BERBAHAN DASAR KERTAS BEKAS BERBASIS KREATIVITAS SISWA PADA MATERI PERUBAHAN IKLIM - Nurul Hidayah Safitri (Jurnal Literasi Pendidikan Dasar (JLPD), 2022)
This study aims to develop a Pop Up Book learning media made of used paper based on students' creativity on climate change material. The research was conducted using a mixed approach, which combines quantitative and qualitative approaches. This research is a study to develop a product or perfect an existing product. The development process refers to a 4-D model (Define, Design, Develop, and Disseminate) which was modified into 3-D only by eliminating the disseminate or deployment stage due to time constraints. The results showed validation with a score of 85% from material experts, 71.42% from media experts, 95% from field experts, from the three experts the results averaged to 83.80%. Student responses to learning using pop up book learning media showed results of 89.19%.